Optimizing Independent Curriculum Management to Shape Excellent Student Character - Hasan Baharun; Abdul Hamid Wahid; Naufal Zakki ‘Aziz Firdaus Udayana; Achmad Anwar Abidin (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2024)
This research analyzes the optimization of independent curriculum management in forming superior student character in madrasas. This research uses a qualitative case study type approach. The data collection technique uses observation, in-depth interviews, and documentation. The data analysis technique uses the Miles, Huberman, and Saldana Interactive Model with data condensation activities, data presentation, and concluding. The triangulation of sources and techniques obtains the validity of the data. The research results show that implementing Independent Curriculum Management to build student character is structured and reasonable. The implementation of Independent Curriculum Management includes five steps, namely increasing the efficiency of using curriculum resources, increasing fairness and opportunities for students, increasing the relevance and effectiveness of learning, increasing the effectiveness of teacher performance and student activities, and increasing the efficiency and effectiveness of the teaching and learning process. These five steps are a process of organizational and functional strengthening of the madrasah for student character. Student character can be influenced by a conducive and collaborative learning culture and learning activities that are proactive and productive in their implementation.